Social Media Use for Youth Mental Health Awareness and Help-Seeking Attitudes: A Systematic Review - Mohamad, Idzreen Nur Fathennadwa; Abd Mubin, Nur Nadia (EDUCATUM Journal of Social Sciences, 2023)
This study provides a systematic review of literature related to social media use for youth mental health awareness and help-seeking attitudes. By adopting the Scientific Procedures and Rationales for Systematic Literature Reviews (SPAR-4-SLR) protocol, 1418 peer-reviewed articles published in academic journals between January 2018 and February 2023 were identified and acquired from Google Scholar and Web of Science databases using keyword searching techniques. The retrieved articles were then organized and purified to exclude the articles that did not meet the inclusion criteria. Of these, only12 articles were eligible for evaluation, using content analysis and thematic analysis. In the context of mental health, our review revealed two themes of social media use, which were for seeking mental health information and seeking emotional support. It was also found that social media use has the potential to enhance mental health awareness and shape positive help-seeking attitudes among youth. Research gaps were identified in relation to the mediation mechanism of mental health awareness through which social media use is related to help-seeking attitudes, particularly in the context of a specific social media visual platform like Instagram. Derived from these findings, we offer research directions to further investigate the role of Instagram in developing youth help-seeking attitudes via mental health awareness.